Respuesta :

r3t40

[tex]

d_f=d_i+v_0t+\dfrac{1}{2}at^2 \\

d_f-d_i-\dfrac{1}{2}at^2=v_0t \\

v_0=\boxed{\dfrac{d_f+d_i-\frac{1}{2}at^2}{t}} \\

[/tex]

Hope this helps.

Answer:

A). [tex]v_{0}=\frac{1}{t}(d_{f}-d_{t}-\frac{1}{2}at^{2})[/tex]

B). [tex]t=\sqrt{\frac{2}{a}(d_{f}-d_{t})}[/tex]

Step-by-step explanation:

The given expression is

[tex]d_{f}=d_{t}+v_{0}t+\frac{1}{2}at^{2}[/tex]

A). We have to solve this expression for the value of [tex]v_{0}[/tex]

[tex]d_{f}-d_{t}=v_{0}t+\frac{1}{2}at^{2}[/tex]

[tex]d_{f}-d_{t}-\frac{1}{2}at^{2}=v_{0}t[/tex]

[tex]v_{0}=\frac{1}{t}(d_{f}-d_{t}-\frac{1}{2}at^{2})[/tex]

B). If [tex]v_{0}=0[/tex] then we have to find the value of t.

We plug in the value of [tex]v_{0}=0[/tex] in the equation in Part A.

[tex]0=\frac{1}{t}(d_{f}-d_{t}-\frac{1}{2}at^{2})[/tex]

[tex]d_{f}-d_{t}-\frac{1}{2}at^{2}=0[/tex]

[tex]\frac{1}{2}at^{2}=d_{f}-d_{t}[/tex]

[tex]t^{2}=\frac{2}{a}(d_{f}-d_{t})[/tex]

[tex]t=\sqrt{\frac{2}{a}(d_{f}-d_{t})}[/tex]

ACCESS MORE